Hydrophilic graphene dispersion liquid for PCB hole metallization and preparation method thereof

Through the synergistic effect of boron-doped graphene and boron-doped graphene quantum dots and polypyrrole, the problems of insufficient conductivity, poor dispersion and poor adhesion in the metallization of PCB plates are solved, achieving high efficiency and low cost The hydrophilic graphene dispersion preparation is suitable for the manufacturing of electronic devices under high temperature environments.

CN119218985AInactive Publication Date: 2024-12-31HUNAN JINYANG GRAPHENE RES INST CO LTD

Patent Information

Application Number
CN202411466923.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-03
Filing Date
2024-10-21
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as insufficient conductivity, poor dispersion, poor adhesion, complex process and high cost in the process of metallization of PCB plate holes, especially the lack of hydrophilicity and high temperature stability of graphene, which limits its Application effect.

Method used

The hydrophilic graphene dispersion is prepared by using boron-doped graphene and boron-doped graphene quantum dots and polypyrrole to synergize with boric acid heat treatment and hydrothermal reaction, and add dispersants and surfactants to form a stable conductive network. Improve conductivity, dispersion and adhesion, and simplify the process flow.

Benefits of technology

It significantly improves the conductivity, dispersion and adhesion of the dispersion liquid, reduces process difficulty and cost, ensures excellent performance under high temperature conditions, and is suitable for high-demand electronic device manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a hydrophilic graphene dispersion liquid for PCB hole metallization, and belongs to the technical field of circuit board processing, the hydrophilic graphene dispersion liquid comprises the following components by mass: 1-5% of boron-doped graphene, 1-5% of boron-doped graphene quantum dots, 10-40% of polypyrrole, 0.5-1% of a dispersant, and 0.5-2% of a surfactant. The second purpose of the invention is to provide a preparation method of the hydrophilic graphene dispersion liquid for PCB hole metallization, the dispersion liquid is subjected to boron doping treatment on graphene and graphene quantum dots, so that the overall conductivity is enhanced, the hydrophilicity is enhanced, the dispersion liquid has excellent dispersity, and the hydrophilicity of the dispersion liquid is improved. Through the synergistic effect of polypyrrole, boron-doped graphene and boron-doped graphene quantum dots, the stability and adhesion of the composite material are further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of circuit board processing, and specifically relates to a hydrophilic graphene dispersion liquid for PCB board hole metallization and a preparation method thereof. Background Art

[0002] In the field of PCB hole metallization, traditional chemical copper deposition or direct electroplating methods have some technical problems, such as the difficulty in controlling the cost of chemical copper deposition, the long process flow, the easy quality risks, and environmental protection issues. In direct electroplating methods, such as the black hole process, the copper plating layer in the obtained hole is uneven and has poor bonding strength. These problems show that the existing technology faces challenges in efficiency, quality and environmental protection when realizing PCB hole metallization.

[0003] Graphene and its derivatives are considered as a potential alternative material for improving the metallization process of PCB holes due to their excellent conductivity, mechanical strength and chemical stability. However, there are also some technical problems in the practical application of graphene, mainly including insufficient conductivity, poor dispersion and poor adhesion to the substrate. For example, after treatment, the conductivity in the hole is prone to unevenness, and the graphene modified material is easy to peel off. These problems limit the application effect of graphene in the metallization process of PCB holes.

[0004] In the existing technology, researchers have added some conductive polymers, such as polyaniline, as a conductive polymer material, which has been widely used in the preparation of graphene composites. Polyaniline can not only significantly improve the conductivity of graphene, but also improve its dispersibility in solution. However, polyaniline still has some limitations in certain application scenarios, such as insufficient adhesion to certain substrates and poor stability in high temperature environments.

[0005] For example, Chinese patent CN115974063A discloses a graphene dispersion for PCB hole metallization and a preparation method thereof, which includes various components: graphene quantum dots, graphene, dispersant and surfactant, which can reduce the structural defects of graphite and achieve high conductivity and high dispersibility, but the hydrophilicity of graphene is not modified, and the adhesion problem between graphene and substrate is not solved. Another example is Chinese patent CN116017885A discloses a graphene copper plating pre-activation liquid based on no dispersant for thick copper PCB hole metallization, which forms π-π adsorption with graphene by graphene oxide rich in carboxyl functional groups and hydroxyl functional groups to hydrophilically modify graphene. The graphene copper plating pre-activation liquid obtained by this method has strong hydrophilicity by modifying the original hydrophobic graphene, so that good dispersion performance can be obtained without using a dispersant, and has the advantage of strong conductivity. However, the modification of graphene oxide in this patent has a great impact on the conductivity of the activation solution, reducing its conductivity, and fails to significantly improve the adhesion and high-temperature stability of the material. Summary of the invention

[0006] In view of the technical defects of the graphene dispersion used for PCB board hole metallization in the prior art, such as complex preparation process, poor dispersibility in solution, weak conductivity, and poor adhesion to the substrate, the first object of the present invention is to provide a hydrophilic graphene dispersion for PCB board hole metallization, wherein the dispersion not only enhances the overall conductivity but also enhances the hydrophilicity by boron doping the graphene and graphene quantum dots, so that the dispersion has excellent dispersibility, and the stability and adhesion of the composite material are further enhanced by the synergistic effect of polypyrrole, boron doped graphene and boron doped graphene quantum dots.

[0007] The second object of the present invention is to provide a method for preparing a hydrophilic graphene dispersion for PCB board hole metallization, which method does not require complicated chemical treatment and high-energy consumption equipment, such as high-temperature heat treatment and high-pressure homogenization, reduces preparation cost and process difficulty, has simple process steps, mild operating conditions, and is easy for industrial production.

[0008] In order to achieve the above technical purpose, the technical solution adopted by the present invention is: A hydrophilic graphene dispersion for PCB board hole metallization comprises the following components in mass percentage: 15-30% of boron-doped graphene, 10-35% of boron-doped graphene quantum dots, 10-40% of polypyrrole, 0.5-3% of dispersant and 0.5-5% of surfactant.

[0009] The hydrophilic graphene dispersion prepared by the present invention exhibits excellent performance in terms of conductivity, dispersibility, adhesion and high temperature stability through the synergistic effect between the components. Boron-doped graphene is prepared by a boric acid heat treatment method, and boron atoms are doped into the carbon skeleton of graphene to form BC bonds. Boron doping improves the conductivity of graphene because boron atoms have lower electronegativity and can provide more free electrons. In addition, the electronegativity of boron atoms is lower than that of carbon atoms, so boron doping causes electrons to be transferred from boron atoms to adjacent carbon atoms to form positively charged boron atoms. This charge transfer increases the polarity of the graphene surface, making it easier to form hydrogen bonds with water molecules, thereby enhancing hydrophilicity and facilitating its dispersion in water. The nanometer size and surface functional groups of boron-doped graphene quantum dots make them have excellent dispersibility and stability. They can be filled in the tiny gaps of PCB board holes, providing more conductive paths, thereby significantly improving the conductivity of the dispersion. Electron transfer occurs between boron-doped graphene and boron-doped graphene quantum dots. Boron doping introduces holes (positive charges) that can move between BG and B-GQDs, thereby enhancing the overall conductivity. BG and B-GQDs together form a continuous conductive network. The nanometer size of B-GQDs enables it to fill the gaps in BG, providing more conductive paths, thereby significantly improving the overall conductivity. At the same time, the addition of dispersants attaches to the surface of graphene and B-GQDs by physical adsorption or chemical bonding to form a stable coating. This coating can effectively prevent the agglomeration of graphene and quantum dots and improve the stability and uniformity of the dispersion. The addition of surfactants forms hydrogen bonds with water molecules through their hydrophilic heads and interacts hydrophobically with graphene and B-GQDs through their hydrophobic tails. This dual effect can significantly reduce the surface tension of the dispersion and improve the dispersibility and stability of graphene and quantum dots. Polypyrrole is a conductive polymer with good conductive properties. Its conductivity comes from the conjugated π electron system, which can form a conductive network in the composite material, significantly improving the overall conductivity. It can also form a stable composite structure with boron-doped graphene and boron-doped graphene quantum dots, improving the stability of the dispersion and preventing the agglomeration of nanomaterials.

[0010] As a further improvement of the above scheme, the boron-doped graphene is prepared by the following steps: heat treating graphene oxide in a boric acid environment at a temperature of 500-800° C. for 2-6 hours to obtain boron-doped graphene.

[0011] As a further improvement of the above scheme, the boron-doped graphene quantum dots are prepared by the following steps: dispersing graphene oxide in deionized water, ultrasonically treating to ensure uniform dispersion, adding boric acid and urea, stirring evenly to form a precursor solution, transferring the precursor solution to a high-pressure reactor, sealing, and conducting a hydrothermal reaction at 180-200° C. for 10-15 hours. After the reaction is completed, cooling to room temperature, filtering the reaction product through filter paper, collecting the filtrate, placing the filtrate in a dialysis bag, dialyzing with deionized water to remove unreacted precursors and by-products, and after the dialysis is completed, centrifuging the dialysate, collecting the supernatant, and drying the supernatant in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

[0012] As a further improvement of the above scheme, the dispersant is one of polyethylene glycol and octadecyltrimethylammonium chloride.

[0013] As a further improvement of the above scheme, the surfactant is one of sodium dodecylbenzene sulfonate, polyvinyl alcohol, sodium cholate, and reduced graphene oxide.

[0014] A method for preparing a hydrophilic graphene dispersion for PCB hole metallization comprises the following steps: mixing boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, a dispersant and a surfactant according to the above mass proportions, and treating the mixed solution with a high shear mixer at a processing speed of 3000-5000 rpm for 20-30 min to obtain a hydrophilic graphene dispersion.

[0015] As a further improvement of the above scheme, the boron-doped graphene and boron-doped graphene quantum dots are respectively subjected to ultrasonic treatment before being added into the mixture, and the frequency of the ultrasonic treatment is 20-40 kHz and the time is 10-30 min.

[0016] As a further improvement of the above scheme, the dispersion is subjected to stabilization treatment after high shear mixing treatment, comprising the following steps: allowing the dispersion to stand for a period of time and observing its stability; if precipitation occurs, performing high shear mixing treatment again until the dispersion is stable.

[0017] As a further improvement of the above scheme, the dispersion is filtered and stored after stabilization treatment, comprising the following steps: filtering the dispersion using a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; storing the filtered dispersion in a sealed container to avoid light and high temperature.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) the boron-doped graphene and boron-doped graphene quantum dots added in the present invention not only significantly improve the conductive properties of the dispersion, but also enhance the hydrophilicity of the dispersion. The synergistic effect of polypyrrole and boron-doped graphene forms a stable conductive network, further enhancing the conductivity. The use of dispersants and surfactants ensures the uniform distribution of graphene and graphene quantum dots in the solution to prevent agglomeration. The application of ultrasonic treatment and high shear mixing technology further improves the stability and uniformity of the dispersion. The present invention introduces polypyrrole as a conductive polymer, and the polypyrrole has a synergistic effect with the boron-doped graphene and the boron-doped graphene quantum dots. The nitrogen atoms in the polypyrrole form NB bonds with the boron atoms on the surface of the boron-doped graphene, thereby enhancing the adhesion between the dispersion and the inner wall of the hole of the PCB board, ensuring the stability and uniformity of the metallization layer, and the NB bonds can promote the transfer of electrons from nitrogen atoms to boron atoms, thereby enhancing the conductivity. The polypyrrole has good stability in a high temperature environment, thereby expanding the application range of the composite material. This high temperature stability enables the dispersion to maintain excellent performance under high temperature conditions; The preparation method of the present invention ensures that boron atoms are effectively doped into graphene and graphene quantum dots through hydrothermal reaction and high-temperature heat treatment, thereby simplifying the process flow; purification steps such as dialysis and centrifugation are used to remove unreacted precursors and by-products, thereby ensuring the purity and stability of the dispersion. Since the dispersion of the present invention exhibits excellent performance in terms of conductivity, dispersibility, adhesion and high-temperature stability, it is suitable for various high-demand electronic device manufacturing fields, especially PCB board hole metallization. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the technical solution, the present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention. Example

[0020] A hydrophilic graphene dispersion for PCB board hole metallization comprises the following components in percentage by mass: 18% boron-doped graphene, 35% boron-doped graphene quantum dots, 40% polypyrrole, 3% polyethylene glycol and 4% sodium dodecylbenzene sulfonate.

[0021] The preparation method of the hydrophilic graphene dispersion in this embodiment is as follows: 10 g of graphene oxide and 5 g of boric acid were weighed and mixed evenly, the mixture was placed in a high-temperature furnace, and heat-treated at 700° C. for 4 h to obtain boron-doped graphene.

[0022] Weigh 1 g of graphene oxide and disperse it in 100 mL of deionized water. Ultrasonic treatment is performed for 30 min to ensure uniform dispersion. 2 g of boric acid and 1 g of urea are added to the graphene oxide solution, and the mixture is stirred evenly to form a precursor solution. The precursor solution is transferred to a high-pressure reactor, sealed, and subjected to a hydrothermal reaction at 190 ° C for 12 h. After the reaction is completed, it is cooled to room temperature. The reaction product is filtered through filter paper, and the filtrate is collected. The filtrate is placed in a dialysis bag and dialyzed with deionized water to remove unreacted precursors and by-products. After the dialysis is completed, the dialysate is centrifuged, the supernatant is collected, and the supernatant is dried in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

[0023] Boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, polyethylene glycol and sodium dodecylbenzene sulfonate are weighed in proportion and mixed, and the mixed solution is treated with a high shear mixer at a processing speed of 3000 rpm for 30 minutes, and then a stabilization treatment is performed, comprising the following steps: the dispersion is allowed to stand for a period of time to observe its stability; if precipitation is produced, high shear mixing treatment is performed again until the dispersion is stable; finally, filtering and storage are performed, comprising the following steps: the dispersion is filtered with a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; the filtered dispersion is stored in a sealed container to avoid light and high temperature to obtain a hydrophilic graphene dispersion; the boron-doped graphene and the boron-doped graphene quantum dots are respectively subjected to ultrasonic treatment before being added to the mixture, and the frequency of the ultrasonic treatment is 20 kHz and the time is 30 minutes. Example

[0024] A hydrophilic graphene dispersion for PCB board hole metallization comprises the following components in mass percentage: 30% of boron-doped graphene, 29% of boron-doped graphene quantum dots, 40% of polypyrrole, 0.5% of octadecyltrimethylammonium chloride and 0.5% of polyvinyl alcohol.

[0025] The preparation method of the hydrophilic graphene dispersion in this embodiment is as follows: 10 g of graphene oxide and 5 g of boric acid were weighed and mixed evenly, the mixture was placed in a high-temperature furnace, and heat-treated at 700° C. for 4 h to obtain boron-doped graphene.

[0026] Weigh 1 g of graphene oxide and disperse it in 100 mL of deionized water. Ultrasonic treatment is performed for 30 min to ensure uniform dispersion. 2 g of boric acid and 1 g of urea are added to the graphene oxide solution, and the mixture is stirred evenly to form a precursor solution. The precursor solution is transferred to a high-pressure reactor, sealed, and subjected to a hydrothermal reaction at 190 ° C for 12 h. After the reaction is completed, it is cooled to room temperature. The reaction product is filtered through filter paper, and the filtrate is collected. The filtrate is placed in a dialysis bag and dialyzed with deionized water to remove unreacted precursors and by-products. After the dialysis is completed, the dialysate is centrifuged, the supernatant is collected, and the supernatant is dried in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

[0027] Boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, octadecyltrimethylammonium chloride and polyvinyl alcohol are weighed in proportion, and the mixed solution is treated with a high shear mixer at a processing speed of 5000 rpm for 20 minutes, and then a stabilization treatment is performed, including the following steps: the dispersion is allowed to stand for a period of time to observe its stability; if precipitation is produced, high shear mixing treatment is performed again until the dispersion is stable; finally, filtering and storage are performed, including the following steps: the dispersion is filtered with a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; the filtered dispersion is stored in a sealed container to avoid light and high temperature to obtain a hydrophilic graphene dispersion; the boron-doped graphene and the boron-doped graphene quantum dots are ultrasonically treated before being added to the mixture, and the frequency of the ultrasonic treatment is 22kHz and the time is 18 minutes. Example

[0028] A hydrophilic graphene dispersion for PCB board hole metallization comprises the following components in mass percentage: 23% boron-doped graphene, 35% boron-doped graphene quantum dots, 35% polypyrrole, 2% polyethylene glycol and 5% sodium cholate.

[0029] The preparation method of the hydrophilic graphene dispersion in this embodiment is as follows: 10 g of graphene oxide and 5 g of boric acid were weighed and mixed evenly, the mixture was placed in a high-temperature furnace, and heat-treated at 700° C. for 4 h to obtain boron-doped graphene.

[0030] Weigh 1 g of graphene oxide and disperse it in 100 mL of deionized water. Ultrasonic treatment is performed for 30 min to ensure uniform dispersion. 2 g of boric acid and 1 g of urea are added to the graphene oxide solution, and the mixture is stirred evenly to form a precursor solution. The precursor solution is transferred to a high-pressure reactor, sealed, and subjected to a hydrothermal reaction at 190 ° C for 12 h. After the reaction is completed, it is cooled to room temperature. The reaction product is filtered through filter paper, and the filtrate is collected. The filtrate is placed in a dialysis bag and dialyzed with deionized water to remove unreacted precursors and by-products. After the dialysis is completed, the dialysate is centrifuged, the supernatant is collected, and the supernatant is dried in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

[0031] Boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, polyethylene glycol and sodium cholate are weighed in proportion and mixed, and the mixed solution is treated with a high shear mixer at a processing speed of 4000 rpm for 23 minutes, and then a stabilization treatment is performed, including the following steps: the dispersion is allowed to stand for a period of time to observe its stability; if precipitation is produced, high shear mixing treatment is performed again until the dispersion is stable; finally, filtering and storage are performed, including the following steps: the dispersion is filtered with a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; the filtered dispersion is stored in a sealed container to avoid light and high temperature to obtain a hydrophilic graphene dispersion; the boron-doped graphene and the boron-doped graphene quantum dots are respectively subjected to ultrasonic treatment before being added to the mixture, and the frequency of the ultrasonic treatment is 40kHz and the time is 10 minutes. Example

[0032] A hydrophilic graphene dispersion for PCB board hole metallization comprises the following components in percentage by mass: 17% of boron-doped graphene, 35% of boron-doped graphene quantum dots, 40% of polypyrrole, 3% of polyethylene glycol, and 5% of reduced graphene oxide.

[0033] The preparation method of the hydrophilic graphene dispersion in this embodiment is as follows: 10 g of graphene oxide and 5 g of boric acid were weighed and mixed evenly, the mixture was placed in a high-temperature furnace, and heat-treated at 700° C. for 4 h to obtain boron-doped graphene.

[0034] Weigh 1 g of graphene oxide and disperse it in 100 mL of deionized water. Ultrasonic treatment is performed for 30 min to ensure uniform dispersion. 2 g of boric acid and 1 g of urea are added to the graphene oxide solution, and the mixture is stirred evenly to form a precursor solution. The precursor solution is transferred to a high-pressure reactor, sealed, and subjected to a hydrothermal reaction at 190 ° C for 12 h. After the reaction is completed, it is cooled to room temperature. The reaction product is filtered through filter paper, and the filtrate is collected. The filtrate is placed in a dialysis bag and dialyzed with deionized water to remove unreacted precursors and by-products. After the dialysis is completed, the dialysate is centrifuged, the supernatant is collected, and the supernatant is dried in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

[0035] Boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, polyethylene glycol and reduced graphene oxide are weighed in proportion and mixed, and the mixed solution is treated with a high shear mixer at a processing speed of 3000 rpm for 25 minutes, and then a stabilization treatment is performed, including the following steps: the dispersion is allowed to stand for a period of time to observe its stability; if precipitation is produced, high shear mixing treatment is performed again until the dispersion is stable; finally, filtering and storage are performed, including the following steps: the dispersion is filtered with a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; the filtered dispersion is stored in a sealed container to avoid light and high temperature to obtain a hydrophilic graphene dispersion; the boron-doped graphene and the boron-doped graphene quantum dots are respectively subjected to ultrasonic treatment before being added to the mixture, and the frequency of the ultrasonic treatment is 28 kHz and the time is 20 minutes. Example

[0036] A hydrophilic graphene dispersion for PCB board hole metallization comprises the following components in mass percentage: 30% of boron-doped graphene, 23% of boron-doped graphene quantum dots, 40% of polypyrrole, 2% of octadecyltrimethylammonium chloride and 5% of sodium dodecylbenzene sulfonate.

[0037] The preparation method of the hydrophilic graphene dispersion in this embodiment is as follows: 10 g of graphene oxide and 5 g of boric acid were weighed and mixed evenly, the mixture was placed in a high-temperature furnace, and heat-treated at 700° C. for 4 h to obtain boron-doped graphene.

[0038] Weigh 1 g of graphene oxide and disperse it in 100 mL of deionized water. Ultrasonic treatment is performed for 30 min to ensure uniform dispersion. 2 g of boric acid and 1 g of urea are added to the graphene oxide solution, and the mixture is stirred evenly to form a precursor solution. The precursor solution is transferred to a high-pressure reactor, sealed, and subjected to a hydrothermal reaction at 190 ° C for 12 h. After the reaction is completed, it is cooled to room temperature. The reaction product is filtered through filter paper, and the filtrate is collected. The filtrate is placed in a dialysis bag and dialyzed with deionized water to remove unreacted precursors and by-products. After the dialysis is completed, the dialysate is centrifuged, the supernatant is collected, and the supernatant is dried in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

[0039] Boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, octadecyltrimethylammonium chloride and sodium dodecylbenzene sulfonate are weighed in proportion and mixed, and the mixed solution is treated with a high shear mixer at a processing speed of 5000 rpm for 20 minutes, and then a stabilization treatment is performed, comprising the following steps: the dispersion is allowed to stand for a period of time to observe its stability; if precipitation is produced, high shear mixing treatment is performed again until the dispersion is stable; finally, filtering and storage are performed, comprising the following steps: the dispersion is filtered with a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; the filtered dispersion is stored in a sealed container to avoid light and high temperature to obtain a hydrophilic graphene dispersion; the boron-doped graphene and the boron-doped graphene quantum dots are respectively subjected to ultrasonic treatment before being added to the mixture, and the frequency of the ultrasonic treatment is 35kHz and the time is 15 minutes.

[0040] Comparative Example 1: Compared with Example 1, the difference in this comparative example is that graphene oxide that has not been doped with boron and graphene oxide quantum dots that have not been doped with boron are added to the graphene dispersion, and the other conditions are consistent with the preparation steps, including the following components in mass percentage: 18% graphene oxide, 35% graphene oxide quantum dots, 40% polypyrrole, 3% polyethylene glycol, and 4% sodium dodecylbenzene sulfonate.

[0041] Comparative Example 2: The difference between this comparative example and Example 1 is that graphene oxide that has not been doped with boron is added to the graphene dispersion, and the other conditions are consistent with the preparation steps, including the following components in mass percentage: 18% graphene oxide, 35% boron-doped graphene quantum dots, 40% polypyrrole, 3% polyethylene glycol, and 4% sodium dodecylbenzene sulfonate.

[0042] Comparative Example 3: The comparative example is compared with Example 1, except that the polypyrrole in the graphene dispersion is replaced by polyaniline, and the other conditions and preparation steps are consistent, including the following components in mass percentage: 18% graphene oxide, 35% boron-doped graphene quantum dots, 40% polyaniline, 3% polyethylene glycol, and 4% sodium dodecylbenzene sulfonate.

[0043] The graphene dispersions obtained in the above Examples 1-5 and Comparative Examples 1-3 were subjected to conductivity test, stability test and particle size test. The conductivity test is to test the resistance after the dispersion is used for hole metallization on the PCB board. The stability test is to test the solid content reduction ratio of the upper suspension after the dispersion is allowed to stand for one week. The particle size test is to test the particle size (D90) growth ratio after the dispersion is allowed to stand for one week. The specific test results are shown in Table 1:

[0044] As can be seen from Table 1, after the dispersion obtained in the embodiment is used for hole metallization of PCB, the measured resistance is as low as 6Ω, while the maximum resistance in the comparative example can reach 3.9KΩ, which has better conductivity, indicating that the addition of boron-doped graphene and boron-doped graphene quantum dots at the same time has better conductivity, and in Comparative Example 3, polyaniline is used instead of polypyrrole, and its conductivity also decreases, indicating that the graphene raw material is subjected to boron doping treatment to introduce holes (positive charge), and these holes can interact with the π electron system in polypyrrole to promote electron transfer and enhance conductivity. This interaction is not obvious in ordinary graphene and graphene quantum dots because they lack holes introduced by boron doping, indicating that there is a synergistic effect between boron-doped graphene, boron-doped graphene quantum dots and polypyrrole.

[0045] A PCB board of standard size was selected to ensure the consistency and cleanliness of the board holes. The hydrophilic graphene dispersions of Examples 1-5 and Comparative Examples 1-3 were evenly coated on the inner wall of the PCB board holes. The coated PCB boards were then placed in a constant temperature and humidity chamber for curing. The bonding strength of the cured PCB board holes was tested using a universal material testing machine. The test results are shown in Table 2:

[0046] As can be seen from Table 2, the dispersion exhibits a higher bonding strength due to the addition of boron-doped graphene, boron-doped graphene quantum dots and polypyrrole, especially the bonding strengths of Examples 1 to 5 are all above 3.0 MPa, which are significantly higher than Comparative Example 1 without boron doping or Comparative Example 3 in which polyaniline is used instead of polypyrrole. This indicates that there is a synergistic effect between boron doping and polypyrrole, and the addition significantly improves the bonding performance of the dispersion to the inner wall of the PCB board hole.

[0047] It should be noted that, in this article, the terms: include, contain and any other variants are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Specific examples are used in this article to illustrate the principle and implementation of the technical solution of the present invention. The above examples are only used to help understand the method of the present invention and its core idea. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements, modifications or changes can be made, and the above technical features can also be combined in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the present invention to other occasions without improvement, should be regarded as the protection scope of the present invention.

Claims

1. A hydrophilic graphene dispersion for PCB hole metallization, characterized in that: The invention comprises the following components in percentage by mass: 15-30% of boron-doped graphene, 10-35% of boron-doped graphene quantum dots, 10-40% of polypyrrole, 0.5-3% of dispersant and 0.5-5% of surfactant.

2. The hydrophilic graphene dispersion for PCB hole metallization according to claim 1, characterized in that: The boron-doped graphene is prepared by the following steps: heat-treating graphene oxide in a boric acid environment at a temperature of 500-800° C. for 2-6 hours to obtain boron-doped graphene.

3. The hydrophilic graphene dispersion for PCB hole metallization according to claim 1, characterized in that: The boron-doped graphene quantum dots are prepared by the following steps: dispersing graphene oxide in deionized water, ultrasonically treating to ensure uniform dispersion, adding boric acid and urea, stirring evenly to form a precursor solution, transferring the precursor solution to a high-pressure reactor, sealing, and performing a hydrothermal reaction at 180-200° C. for 10-15 hours. After the reaction is completed, cooling to room temperature, filtering the reaction product through filter paper, collecting the filtrate, placing the filtrate in a dialysis bag, dialyzing with deionized water to remove unreacted precursors and by-products, and after the dialysis is completed, centrifuging the dialyzate, collecting the supernatant, and drying the supernatant in a vacuum drying oven to obtain solid boron-doped graphene quantum dots.

4. The hydrophilic graphene dispersion for PCB hole metallization according to claim 1, characterized in that: The dispersant is one of polyethylene glycol and octadecyltrimethylammonium chloride.

5. The hydrophilic graphene dispersion for PCB hole metallization according to claim 1, characterized in that: The surfactant is one of sodium dodecylbenzene sulfonate, polyvinyl alcohol, sodium cholate, and reduced graphene oxide.

6. A method for preparing a hydrophilic graphene dispersion for PCB hole metallization according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing boron-doped graphene, boron-doped graphene quantum dots, polypyrrole, a dispersant and a surfactant according to the above mass proportion, treating the mixed liquid with a high shear mixer at a processing speed of 3000-5000 revolutions / min for 20-30 minutes to obtain a hydrophilic graphene dispersion.

7. The method for preparing a hydrophilic graphene dispersion for PCB hole metallization according to claim 6, characterized in that: The boron-doped graphene and boron-doped graphene quantum dots are respectively subjected to ultrasonic treatment before being added into the mixture, and the frequency of the ultrasonic treatment is 20-40 kHz and the time is 10-30 minutes.

8. The method for preparing a hydrophilic graphene dispersion for PCB hole metallization according to claim 6, characterized in that: The dispersion is subjected to stabilization treatment after the high shear mixing treatment, comprising the following steps: allowing the dispersion to stand for a period of time and observing its stability; if precipitation occurs, performing high shear mixing treatment again until the dispersion is stable.

9. The method for preparing a hydrophilic graphene dispersion for PCB hole metallization according to claim 8, characterized in that: The dispersion is filtered and stored after stabilization treatment, comprising the following steps: filtering the dispersion using a microporous filter membrane to remove undispersed boron-doped graphene and boron-doped graphene quantum dot particles; storing the filtered dispersion in a sealed container to avoid light and high temperature.

Citation Information

Patent Citations

  • Preparation method for boron-doped graphene

    CN103896258A

  • Method for preparing boron-doped graphene quantum dots through liquid-phase reaction

    CN106560445A

  • Preparation method of boron-doped graphene / polypyrrole composite aerogel with compression recovery property

    CN108568277A

  • Method for preparing graphene dispersion liquid under assistance of quantum dots

    CN109305675A

  • Graphene dispersion liquid for PCB hole metallization and preparation method thereof

    CN115974063A

Cited By

  • PCB hole metallization black shadow reagent based on graphene quantum dots as well as preparation method and application of PCB hole metallization black shadow reagent

    CN121442581A

  • A graphene quantum dot-based PCB hole metallization black shadow reagent, a preparation method thereof and application thereof

    CN121442581B